Um estudo sobre a percepção de estudantes de Engenharia da Computação sobre a relação entre tópicos de Introdução a Programação e os pilares do Pensamento Computacional - Santos, Adriano Brito dos (2023)
A solid and well-built base in basic education can have a remarkable reflection in graduation, therefore, it is necessary to encourage the development of skills that involve the elements of computational thinking since the early years of elementary school. This paper analyzes the perception of Computer Engineering students regarding the teaching of computational thinking in basic education, focusing on the subject of Introduction to Programming. Through bibliographic research and online questionnaires, the study seeks to understand how students perceive the topics and skills developed in this subject over time. The questionnaire, divided into three blocks, addressed the profile of the students, the perception of skills related to the pillars of Computational Thinking, and the correlation between Mathematics and Introduction to Programming. Responses were collected from 20 students, revealing that 11 had had previous contact with programming and nine had not. It was observed that some students with no previous programming experience faced greater initial difficulties in the subject, highlighting the importance of teaching approaches that facilitate the insertion of these students in the context of computational thinking. In sum, this study provides a comprehensive view of Computer Engineering students' perceptions regarding the teaching of computational thinking in basic education. It highlights the importance of the subject of Introduction to Programming in developing essential skills for the computing field and highlights the need for teaching strategies suitable for students with no prior programming experience.